If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -1(156 + -1X) = 78 X + (156 * -1 + -1X * -1) = 78 X + (-156 + 1X) = 78 Reorder the terms: -156 + X + 1X = 78 Combine like terms: X + 1X = 2X -156 + 2X = 78 Solving -156 + 2X = 78 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '156' to each side of the equation. -156 + 156 + 2X = 78 + 156 Combine like terms: -156 + 156 = 0 0 + 2X = 78 + 156 2X = 78 + 156 Combine like terms: 78 + 156 = 234 2X = 234 Divide each side by '2'. X = 117 Simplifying X = 117
| 3x-24+2x=2x | | 38x+85=38x+78 | | x2=49/81 | | 5x+4(-3x-10)=103 | | 3/4(2x–8) | | X/-1/6=6/7 | | x^2+4x-8y+12=0 | | -5(f-929)=85 | | P+2p+3p+2=2 | | 7x+23x-4=6(5x+9) | | 18(w+25)=468 | | 4x-2(1+2x)=6 | | 3.4w=9.7 | | 34x+3y=12 | | 2x(-40)=x | | 0.8k=1.36 | | 3=w-5/4 | | f(1)=-12 | | a+3b=4ab | | -2a-3a+1=6 | | 356/16=267/x | | -2x+4x-28=-2x+3x-12 | | 14-y=17 | | 8n+(-6n)= | | 247/26=209/x | | 4r^2-12r-160=0 | | -2x(x+5)=0 | | 8y-3=8y-5 | | 3(z-12)=9 | | 2x-50=62 | | 8n+(-6n)+(-9)-12= | | 20/3n=3/4 |